Guillain Barre Syndrome as a Presentation of post Covid-19 Infection among Children: A Case Series - Onkareshwar, Kavthekar Saiprasad; Ravso, Patil Rahul; Susmitha, Narahari Venkata; Maruti, Jadhav Vilas; Balasaheb, Patil Nivedita; Bapurao, Kurane Anil (Journal of Nepal Paediatric Society, 2022)
During the second wave of Covid-19 pandemic, children presented with myriad of central nervous system manifestations and one of them was Guillain-Barré syndrome (GBS). It is caused by various viruses including recent Covid-19 infection by either direct invasion or post infectious process. Most of these cases were reported in adults and very few in children. Here, we report a case series of five children with GBS along with positive Covid-19 antibodies, probably first from India. All patients responded well to intravenous immunoglobulin without any residual weakness. Hence, we could probably link casual association of Covid-19 infection with GBS.